The surprising photochemistry of sultams related to saccharin - Dietrich Döpp (International Journal of Photoenergy)
The known light induced reactions of sulfonamides and sultams are in most (but not all) cases initiated by S–N homolysis. Sulfur dioxide release may be a consequence of this primary process. In the author's laboratory three hitherto unexplored photoreactions of saccharin-derived sultams have been investigated: (i) a novel formal oxygen shift from sulfur to nitrogen generating upto now unknown cyclic N-hydroxysulfinamides; (ii) a condensative dimerization of 2,3-dihydro-1,2- benzoisothiazole 1,1-dioxide generating a new cleft molecule, and (iii) a facile allylic skeletal rearrangement of a pyrrolo-anellated dihydro- 1,2-benzoisothiazole. At least in the latter two cases an initial S–N-homolysis seems to be vital for the processes observed, whereas in the first case some ambiguity remains with respect to the first step. Scope and limitations are discussed and rationales for the conversions observed are presented, with special emphasis on structure proof by X-ray crystal structure determinations. All reactions discussed have to be treated within the wider context of current sulfonamide and sultam photochemistry.